Proximate and ultimate analysis of empty fruit bunch and Shorea SP. Woods: article - Mohd Fuaad, Izzat Fitri; Alias, Rusmi (2017)
This project aimed to analyse and characterize the empty fruit bunch (EFB) of oil palm and shorea sp. wood in the area under study through the proximate and ultimate analysis. The proximate analysis consists of analytical evaluation of properties such as moisture content, fixed carbon, volatile matter and ash content of the EFB. Based on the recent study, the moisture content in the unprocessed EFB of oil palm ranges around 67% while moisture content for processed EFB ranges between 30% to 50% (Salman zafar, 2015).The volatile matter varies from 71.2% to 79.7%, the ash content ranges between 3.02 – 7.54% and the fixed carbon content ranges between 8.65 – 18.3% (Rozita Omar, 2011). The ultimate analysis is quantitative analysis of various elements present in a sample, such as carbon, hydrogen, sulphur, oxygen, and nitrogen (Ultimate and Proximate Coal Analysis, n.d.).The concentration of carbon for EFB ranges between 45 – 48.8% , the oxygen content varies from 40.2 – 47.3%, hydrogen ranges between 6.4 – 7.33%, nitrogen ranges between 0.0 – 0.25% and the sulphur content varies from 0.68 to 1.06% (Rozita Omar, 2011). Moreover, the proximate and ultimate analyses when interpreted in detail may form an effective tool to characterize the EFB.